2012
DOI: 10.1186/1471-2288-12-25
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for and against participation in studies of medicinal therapies for women with breast cancer: a debate

Abstract: BackgroundA special challenge for research studies of breast cancer among females is low patient participation rates. We compiled this systematic review to identify reasons why women with, or at high risk of, breast cancer do or do not participate in medicinal studies of breast cancer.MethodA systematic literature search in the databases Cochrane Library, EMBASE, Medline, Pascal Biomed, ACP Journal Club and CINAHL, as well as searches through reference lists of relevant texts, was performed.ResultsOf 39 releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…This contrasts with a review of reasons among healthy volunteers to participate in clinical trials in mainly high-resource settings (United States (n studies = 6), Portugal, Spain, the Netherlands, Croatia, Germany, United Kingdom and Malawi (all n = 1), in which financial rewards were reported a primary motivation to participatealbeit altruistic motives informed the decision as well [118]. For specific (patient) populations in high-resource settingschildren and their parents participating in drug research, women with breast cancer, cancer patients and minority populations in the United Statesaltruism and access to health care were (more) important considerations in the decision to participate in research [5][6][7][8]118].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with a review of reasons among healthy volunteers to participate in clinical trials in mainly high-resource settings (United States (n studies = 6), Portugal, Spain, the Netherlands, Croatia, Germany, United Kingdom and Malawi (all n = 1), in which financial rewards were reported a primary motivation to participatealbeit altruistic motives informed the decision as well [118]. For specific (patient) populations in high-resource settingschildren and their parents participating in drug research, women with breast cancer, cancer patients and minority populations in the United Statesaltruism and access to health care were (more) important considerations in the decision to participate in research [5][6][7][8]118].…”
Section: Discussionmentioning
confidence: 99%
“…Others looked into practical aspects in an attempt to understand barriers for research participation and improve recruitment and retention rates [1][2][3][4]. Studies on the willingness to participate include research in specific populations such as pregnant women or children with cancer, ethnic minorities, and in varying contexts in high as well as low-and middle-income countries (LMICs) [2,[5][6][7][8][9]. Systematic reviews on willingness to participate are rare [7,10], and do not exist for research participation in LMICs specifically.…”
Section: Introductionmentioning
confidence: 99%
“…Participants indicated the importance of a supportive research team that is willing to accommodate their meeting preferences. Several studies have indicated that offering flexible and convenient options to meet with the research team enhances the participants’ experience and retention (Luschin, Habersack, & Gerlich, ; Mein et al., ; Tallon et al., ; Theadom et al., ). One participant indicated he participated and remained in the study because study staff was so effective in “tracking me down.” Although this response could be interpreted negatively as “pestering” research participants, longitudinal studies require tenacity in reaching out to participants to maximize retention.…”
Section: Discussionmentioning
confidence: 99%
“…a dislike of randomization, preference for a certain treatment, or fear of being a guinea pig. 7–9 Such reasoning may be based on a poor understanding of clinical research. Numerous studies have tried to find out what patients really know by focusing on their comprehension of the information given in informed consent or by assessing their understanding before and after receiving educational material.…”
Section: Introductionmentioning
confidence: 99%